2005
DOI: 10.1614/ws-04-036r
|View full text |Cite
|
Sign up to set email alerts
|

Interference interactions of two rice cultivars and their F3cross with barnyardgrass (Echinochloa crus-galli) in a replacement series study

Abstract: Barnyardgrass (BYG) has been the most frequently reported troublesome weed in rice because it is an aggressive invader, is difficult to control, and reduces yields significantly. A replacement series study was conducted to determine how a naturally suppressive cultivar (T65∗2/TN 1; ‘PI 312777’), a nonsuppressive cultivar (‘Lemont’), and an F3 cross between the two (‘PI 312777 × Lemont’) would interfere with BYG in the southern United States. The rice cultivars did not differentially affect BYG height. The PI 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…RYT values less than 1 suggest there is mutual antagonism between the two species (Harper 1977;Radosevich 1987). The relative crowding coefficient (RCC), which serves as an index of competition when the two species are competing at equal proportions (Gealy et al 2005), was calculated at the 3 : 3 mixture using the following equation: [2]…”
Section: Methodsmentioning
confidence: 99%
“…RYT values less than 1 suggest there is mutual antagonism between the two species (Harper 1977;Radosevich 1987). The relative crowding coefficient (RCC), which serves as an index of competition when the two species are competing at equal proportions (Gealy et al 2005), was calculated at the 3 : 3 mixture using the following equation: [2]…”
Section: Methodsmentioning
confidence: 99%
“…The importance of rice-barnyardgrass allelopathic interactions, as well as the mechanisms underlying such interactions, have been a major focus of non-herbicidal alternative barnyardgrass management in recent years. [18][19][20]23 However, most studies on interference of allelopathic rice with barnyardgrass have not clearly distinguished between herbicide-resistant and -susceptible biotypes. This study identifies penoxsulam-resistant and -susceptible barnyardgrass biotypes with the same genetic background from Chinese rice fields, and highlights allelopathic rice and the potential effect of its allelochemicals against penoxsulam-resistant barnyardgrass.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to control them have met with limited success. An increasing number of studies have shown that allelopathic rice cultivars release allelochemicals to interfere with the growth and establishment of coexisting barnyardgrass . Through the release of allelochemicals, allelopathic rice cultivars can suppress barnyardgrass and provide a competitive advantage for their own growth .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades much effort has focused on the use of allelopathic rice cultivars as an efficient component of integrated weed management in paddy systems (Gealy et al . ; Kong et al . ; Pheng et al .…”
Section: Introductionmentioning
confidence: 99%